PENGENDALIAN KUALITAS KINERJA LEVEL SIX SIGMA PADA PT INDOFOOD CBP SUKSES MAKMUR TBK MAKASSAR - Faradiba Ahmad; Muhammad Arif Tiro; Muhammad Kasim Aidid (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2021)
Six Sigma is a combination of several statistical quality control methods that focus on reducing variations in the process so that it can suppress production in the form of goods or services to approach zero defects. The six sigma systematic stages are called DMAIC (Define, Measure, Analyze, Improve, and Control) which is a continuous process which, if carried out optimally throughout the system, can increase the productivity of a company. There are four kinds of quality characteristics or CTQ in the production of instant noodles at PT Indofood CBP Sukses Makmur Tbk Makassar. The four CTQs are HH, HP, HHPGK, and HHPG. The CTQ was then implemented using the six sigma method and the DPMO values from October-December 2019 were as follows 4,457.90, 5,404.26, and 4,827.45 and if the DPMO value was converted to the six sigma level it would be 4.11σ, 4.04σ, and 4.08σ. To increase the productivity of related companies to approach zero defects, the application of the six sigma method must be carried out optimally so that the sigma level of instant noodle production can increase.Keywords: Regression, resampling, bootstrap, jackknife